Emotional and physiological processes and positive intervention strategies - Perrewe, Pamela L.; Ganster, Daniel C. (Research in occupational stress and well being, 2003)
This is an annual research series devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. The intent is to pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. A multidisciplinary and international perspective is provided to give a thorough and critical assessment of issues in occupational stress and well being. The theme for this volume is: emotional and physiological processes and positive intervention strategies.